The Religious Meaning of “Kulut Kaet” (Mourning Lament) in Dawan Ethnic in Nusa Village In East Nusa Tenggara: An Ethnographic Perspective Study - Isu, Rudolof Jibrael; Yanrini M. Anabokay; Ni Putu Juliani Lestari Dewi; Yennsy M. Fanggidae; Rocky P. Sekoni; Markus D. Radja; Temy M. E. Ingunau; Agnes O. Manek (E-Link Journal, 2025)
Kulut kaet, or mourning lament, is an important tradition in the Dawan ethnic community in South Central Timor District, East Nusa Tenggara (NTT), which carries deep religious significance. It is more than just an expression of grief over loss, but also a means of honoring the spirit of the deceased and maintaining the connection between the living world and the spiritual world. This article aims to explore the religious significance of the Kulut kaet emphasizing the spiritual dimension of the mourning ritual. Through a qualitative and ethnographic approach, this study analyses how Kulut kaet functions as a form of respect for the spirits of the deceased, as a way of maintaining relationships with ancestors, as well as a collective healing mechanism for the Dawan community. The results show that Kulut kaet is not only an expression of personal grief, but also a ritual that involves the community in the process of grieving together. This lament becomes important in strengthening social solidarity, preserving traditions, and carrying out religious obligations as a tribute to the spirits of the deceased.